Essentials of materials science and engineering - Askeland, Donald R.; Wright, Wendelin J.; Bhattacharya, D. K. (Cengage Learning, 2014)
This text provides students with a solid understanding of the relationship between the structure, processing, and properties of materials. Authors Askeland and Wright present the fundamental concepts of atomic structure and the behavior of materials and clearly link them to the "materials" issues that students will have to deal with when they enter the industry or graduate school (e.g. design of structures, selection of materials, or materials failures). Fundamental concepts are linked to practical applications, emphasizing the necessary basics without overwhelming the students with too much of the underlying chemistry or physics.